Icts and their implications in human rights formation - Fernández Umaña, Diana Isabel; Rodríguez Meléndez, Eduard Humberto (Rastros Rostros, 2012)
This paper is centered on the subject of an ongoing research project proposed to the Faculty of Law of the Universidad Cooperativa de Colombia at Bucaramanga, so that it will work as an observatory for the ample andcomplex aspects of the protection and promotion of international law on human and environmental rights. The program “Education in and for human rights” encompasses four main micro-projects that may be developed in an interdisciplinary fashion and with mutual and congruent projections
Keywords: International human and environmental rights; Interdisciplinary; Institutional platform; Virtual reality; Ict